الفشتاليين في المغرب الاقصى و دورهم في الحياة العامة - العثمان، إيمان عبدالرحمن حسن (جامعة الموصل - كلية العلوم الإسلامية, 2013)
اشتهرت أسر مرموقة في المغرب الأقصى بمكانه اجتماعية، رفيعة المستوى لدى اولي الأمر ولدى عامة الشعب. \ ولا شك في ان المكانة التي اكتسبتها قسم من هذه الأسر تعود إلى عدة أسباب منها الثروة التي امتلكوها والمكانة العلمية التي تمتعوا بها، ولنسبها الشريف ،أو لاحتكارها وظائف رسمية. \ ويعد بنو فشتال من ابرز هذه الأسر الذين ظهرت في المغرب الأقصى في عصر المرينيين (668هـ-869هـ/1269م-1465م) وتمكنوا بفضل ما تمتعوا به من حنكة سياسية من الوصول إلى المراكز المهمة والمتقدمة في الدولة في عصر ما بعد المرينيين ولاسيما في عهد الدولة السعدية (956هـ- 1022هـ/ 1510م-1659م)، وقد كان لهم دور كبير في الحياة الثقافية واستلمت شخصيات من هذا البيت مناصب في الدولة وتركوا خلفهم بصمات واضحة في مجالات مختلفة فكان منهم القاضي والسفير والفقيه الأديب وقبل كل هذا كان لهم دور ديني واجتماعي متميز. \ وسيتناول هذا البحث إيضاح دور (الفشتاليين) في المغرب الأقصى في عهد المرينين وهو عهد بروزهم وفي عهد الدولة السعدية إذ تبؤا أهم المناصب وكانت لهم مكانة كبيرة في البلاط السعدي حيث أصبحوا أعلام تلك الدولة آنذاك. Prestigious houses in far Morocco were famous for their high level social status for the rulers and the common people . \ There is no doubt that the status obtained by some of those houses was due to several reasons like the wealth possessed by them , the scientific status enjoyed by them , noble origin or possessing official positions . \ Banu Fashtals were considered the most significant house appeared in far Morocco in the Age of Marinids (668 – 869 A.H. / 1269 – 1465 A.D.) . Being enjoyed by their statesmanship , they could access important and advanced positions in the state in the age of Mairinds , especially in the age of Saadia State (956 A.H. – 1022 / 1510 A.D. – 1659). They had great role in the cultural life and some figures of that house had accessed good positions in the state and left clear marks in various fields . them was judges , ambassador, jurist and authors .Moreover, they had distinguished religious and social role . \ This research deals with the role of the Fashtals in Far Morocco at the age of Mairinds , the age of their prominence , and at the age of Saadia State . They accessed important positions and great position in the Saadian court .They became top figures in the Saadia State .
Keywords: الفشتاليون -- الدولة المرينية -- المغرب العربي -- الدولة السعدية